Non-invasive biomarkers of perioperative stress in ophthalmic surgeons: Heart rate variability, cortisol and salivary copeptin in a feasibility study - Rubén Cabrera Beyrouti; Marina López-García; María Eugenia Torregrosa Quesada; Jorge Francés Ferre; Ezequiel Campos-Mollo; Rocío Alfayate Guerra; Adolfo Aracil-Marco (PLoS ONE, 2026)
Surgeons are exposed to acute perioperative stress that may compromise performance and patient safety. Objective, non-invasive biomarkers are essential to quantify and manage this stress. This prospective, quasi-experimental feasibility study aimed to describe the acute dynamics of heart rate (HR), heart rate variability (HRV), salivary cortisol, and salivary copeptin in ophthalmic surgeons during routine cataract surgery, while assessing the feasibility of measuring copeptin in human saliva for the first time. Fifteen ophthalmologists from three public hospitals were assessed on a resting day (baseline) and on a surgical day involving routine cataract procedures. HR and HRV (SDNN, RMSSD, pNN50, LF/HF) were recorded with a Polar H9 chest strap and a validated mobile application, and saliva samples were collected for cortisol and copeptin (a neurohormone released by the posterior pituitary gland) at four perioperative time points (arrival at hospital, pre-scrub, immediately post-surgery, and 30 min post-surgery). Repeated-measures analyses and correlation tests were performed. At rest, participants showed a mean HR 72.5 ± 15 beats·min ⁻ ¹ and salivary cortisol 0.41 ± 0.29 µg·dl ⁻ ¹, and detectable salivary copeptin levels (2.3 ± 0.7 pmol·l ⁻ ¹). On the surgical day, HR (66.6 ± 8.8 beats·min ⁻ ¹) and cortisol (0.21 ± 0.10 µg·dl ⁻ ¹) decreased significantly at 30 min post-surgery compared with pre-intervention values (74.0 ± 11.3 beats·min ⁻ ¹ and 0.47 ± 0.30 µg·dl ⁻ ¹, respectively), consistent with stress relief, while HRV indices displayed inverse patterns. Although a slight elevation in copeptin levels was observed during the surgical day (from 2.07 ± 0.42 at baseline to 2.50 ± 0.67 2.3 ± 0.7 pmol·l ⁻ ¹ immediately before surgery), this change did not reach statistical significance. In conclusion, the performance of routine cataract surgery triggers specific neuroendocrine responses in ophthalmologists. These findings support the use of multi-modal biomarkers to monitor perioperative strain and its potential impact on surgical performance.